Pembiayaan Jangka Pendek dan Pembiayaan Jangka Panjang Keuangan Internasional - Wahidah Nazmi Lailia; Fadlillah Ramadhan; Wildan Fathil Padil; Perwito Perwito (Indo Publishing, 2026)
The importance of short-term and long-term financing in international financial management as part of a business strategy to address global economic changes. Short-term financing is typically used to meet liquidity and working capital needs, particularly for cross-border activities such as exports and imports, using instruments such as trade credit, international trade paper, Euro-denominated loans, and internal financing. Meanwhile, long-term financing facilitates major investments, business expansion, and strengthens a company's capital structure, with bonds being the primary instrument. This article also discusses various strategic considerations taken into account when selecting international financing sources, such as the cost of funds, exchange rate fluctuations, interest rate parity, and global financial risks, including exchange rate, interest rate, liquidity, and political risks. Case studies of short-term and long-term financing demonstrate that effective risk management, such as hedging strategies, and thorough analysis are necessary for making informed international financing decisions. Therefore, effective international financing management can help maintain financial stability, improve efficiency, and enhance business competitiveness in the global market.